Physical and sensory properties of boiled rice treated with emulsifiers - Espinosa, Catherine A. (2006)
ABSTRACT This study aimed to assess the effects of emulsifiers on boiled Philippine Seed Board Rice (PSBRc) varieties 14 and 66. The emulsifiers used were Sodium Lauryl Sulfate (SLS). Tween 80, cottonseed oil. Tween 80-cottonseed oil emulsion and, glycerin. The treatments tested indicated that rice grain washed with SLS and then cooked with the other emulsifiers were more elongated but less expanded, lighter in weight and, lesser in moisture content than the untreated control boiled rice. Likewise, the treated samples showed incomplete gelatinization, as indicated by chalky centers except for samples washed with SLS and have glycin in its cooking medium. Sensory evaluation results indicated that boiled rice washed with SLS and cooked with glycerin had the highest overall acceptability because it was established to be more moist, cohesive and softer than all other treated boiled rice samples but not relative to the untreated control samples. Cell morphology test results indicated that treated boiled rice samples developed smaller or even complete absence of grain hollows relative to the untreated control samples. One unique impact that was noted for boiled rice treated with both SLS and glycerin was the apparent disintegration of the cell walls of almost all of the outer endosperm and a number of cells of the inner endosperm of its cooked grain. It can be recommended that emulsifiers, especially SLS with glycerin, can be used in rice processing methods to improve the eating quality and help preserve the integrity of the rice grains.